PPS composite material as well as preparation method and application thereof
By controlling the glass fiber length and optimizing the component ratio of PPS composite materials, the problem of insufficient strength and toughness of existing magnetic PPS materials has been solved, realizing a high-performance material with a metallic knocking feel and magnetic attraction function in the toy industry.
Patent Information
- Application Number
- CN202511205738.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-11-11
AI Technical Summary
Existing magnetic PPS composite materials filled with metal magnetic powder have poor mechanical properties, making it difficult to meet the toy industry's requirements for material strength and toughness.
By controlling the average retention length of glass fibers within the range of 200-400μm, and using appropriate amounts of metallic fillers, PPS resin, and toughening agents, the component ratio and processing technology of PPS composite materials are optimized to ensure that the material has good strength and toughness while possessing a metallic knocking feel and magnetic attraction function.
The prepared PPS composite material retains the metallic knock feel and magnetic attraction while significantly improving the material's strength and toughness, meeting the application needs of the toy industry.
Smart Images

Figure BDA0005567647090000071 
Figure BDA0005567647090000081
Abstract
Description
Technical Field
[0001] This invention belongs to the field of engineering plastics technology, specifically relating to a PPS composite material, its preparation method, and its application. Background Technology
[0002] Polyphenylene sulfide (PPS) resin is a specialty engineering plastic with excellent heat resistance, chemical resistance, flame retardancy, mechanical strength, electrical properties, and dimensional stability. Based on these properties, PPS is well-suited for applications that replace steel with plastic. In the toy industry, due to the industry's specific requirements, when replacing steel with plastic, the material is required to have a metallic feel and magnetic properties. Furthermore, based on application needs, the injection-molded parts must possess good strength and toughness to meet assembly, design, and usage requirements.
[0003] Magnetic PPS products modified with metal magnetic powder can enhance the metallic impact feel of materials while also giving them magnetic attraction capabilities, thus meeting the requirements for both metallic impact feel and magnetic attraction. However, existing magnetic PPS composite materials filled with metal magnetic powder have poor mechanical properties, making it difficult to meet the requirements for mechanical performance.
[0004] Therefore, developing a PPS composite material that can satisfy the requirements of metallic knocking texture and magnetic attraction while also possessing good strength and toughness is an urgent problem to be solved in this field. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, the present invention aims to provide a PPS composite material, its preparation method and application. This PPS composite material has the characteristics of metallic impact, high strength and magnetic attraction, making it very suitable for use in the toy industry.
[0006] This invention is achieved through the following technical solution:
[0007] This invention provides a PPS composite material, which, by weight, comprises 100 parts of metallic filler, 20-40 parts of glass fiber, 50-80 parts of PPS resin, and 2-8 parts of toughening agent, wherein the average retention length of the glass fiber in the PPS composite material is 200-400 μm, preferably 250-370 μm.
[0008] The present invention provides a method for testing the average retention length of glass fibers in PPS composite materials: 3-5g of PPS composite material sample is calcined at 700℃ to remove PPS resin. The ash is then dispersed evenly in distilled water and stirred thoroughly before being uniformly dispersed in a petri dish. The glass fiber length is measured using an optical microscope at multiple random fields of view, ensuring sufficient coverage of glass fibers (at least 150 fibers must be measured). The arithmetic mean of all measured lengths is calculated, representing the average retention length of the glass fibers.
[0009] This invention unexpectedly discovered that in PPS composite materials filled with metallic fillers, by controlling the average retention length of glass fibers within the range of 200-400 μm (for example, it can be 210 μm, 230 μm, 245 μm, 250 μm, 265 μm, 280 μm, 305 μm, 321 μm, 330 μm, 345 μm, 360 μm, 375 μm, 385 μm, 400 μm or any of the above values), the PPS composite material can possess both a metallic feel and magnetic properties, while also exhibiting good strength, toughness, and appearance, thus meeting the needs of the toy industry.
[0010] In PPS composites, if the average retention length of the glass fibers is too long, the material will have more loose fibers and a poor appearance. If the average retention length of the glass fibers is too short, the mechanical properties will be poor and will not meet the performance requirements.
[0011] Those skilled in the art can adjust the degree of shearing experienced by the glass fiber through various means, thereby controlling the average retention length of the glass fiber in the PPS composite material within the range of 200-400 μm. For example, this can be achieved by controlling the addition ratio of the glass fiber main side feed, or by adjusting the shearing of the screw and the screw speed.
[0012] Preferably, the glass fiber can be chopped E glass round fiber, chopped E glass flat fiber, chopped D glass round fiber, or chopped D glass flat fiber.
[0013] In the PPS composite material of the present invention, the mass percentage of glass fiber is 8%-22% (for example, it can be 9%, 10%, 12%, 14%, 15%, 18%, 20%, 22% or any range between the above proportions).
[0014] Preferably, according to ISO 1133-1-2022 testing, under conditions of 300℃ and 2.16KG, the melt index of the PPS resin is 50-200g / 10min, for example, it can be 50-60g / 10min, 60-70g / 10min, 70-85g / 10min, 85-100g / 10min, 105-120g / 10min, 135-150g / 10min, 180-200g / 10min or any range between the above values, preferably 60-100g / 10min.
[0015] The preparation method of PPS resin typically involves dehydrating sodium hydroxide, N-methylpyrrolidone, and sodium hydrosulfide to obtain a sodium sulfide-containing mixture. This sodium sulfide-containing mixture is then mixed with p-dichlorobenzene (PDCB) and polymerized under high temperature and pressure. PPS resin prepared in this way inevitably contains salt impurities such as sodium chloride. These impurities adversely affect the resin's properties, especially its electrical properties. Therefore, to date, PPS resin has been treated with multiple water washes or a combination of water washing and organic solvent washing to reduce the sodium ion impurity content before application.
[0016] However, through unexpected research, this invention discovered that the lower the sodium ion content in PPS resin, the stronger the acidity of the resin, which in turn leads to a decrease in the mechanical properties of composite materials containing PPS resin.
[0017] This invention controls the sodium content in the PPS composite material to be between 230-800 ppm by weight (e.g., 230 ppm, 300 ppm, 400 ppm, 450 ppm, 500 ppm, 700 ppm, 750 ppm, 800 ppm, or any value between these ranges), thus enabling the composite material to possess good mechanical properties. Preferably, the sodium content in the PPS composite material is 300-700 ppm by weight.
[0018] The present invention can control the specific range of sodium content in PPS composite materials by adding PPS resin containing different amounts of sodium or by adjusting the amount of PPS resin and glass fiber added.
[0019] This invention does not impose any particular limitations on the methods for making PPS resin contain different amounts of sodium. For example, the sodium can be derived from commercially available products, or it can be adjusted by adding a specified amount of a sodium-containing compound to the PPS resin, or by repeated washing with water or a combination of water washing and organic solvent washing after the PPS resin is prepared. The sodium-containing compound includes sodium hydrosulfide, sodium chloride, etc.
[0020] The method for detecting the sodium content by weight according to the present invention is as follows: Weigh 0.1g of sample into a polytetrafluoroethylene (PTFE) container, add 5ml of 65% nitric acid, 1.5ml of 30% hydrogen peroxide, and 0.5ml of 70-72% perchloric acid, and cover the container. Place the PTFE container into a stainless steel high-pressure digestion vessel, and react the digestion vessel at 210-230℃ for 120min. Cool to room temperature and dilute to 50ml with ultrapure water. Quantitative analysis of sodium is performed using ICP-OES.
[0021] Depending on the object being tested, the sample may be PPS resin powder, PPS composite material powder, or glass fiber powder.
[0022] The above-mentioned methods for detecting the sodium content by weight are all applicable to the determination of sodium content in PPS resin, PPS resin compositions, or glass fibers.
[0023] In the PPS composite material of the present invention, PPS resin is used as the matrix resin, and the mass percentage content of PPS resin is 25-40% (for example, it can be 25%, 27%, 30%, 32%, 35%, 37%, 39%, 40% or any range between the above proportions).
[0024] Preferably, the average retained particle size of the metallic filler is 10-60 μm (e.g., it can be 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 24 μm, 27 μm, 30 μm, 32 μm, 36 μm, 38 μm, 40 μm, 44 μm, 50 μm, 55 μm, 60 μm or any range between the above proportions), and more preferably 20-50 μm.
[0025] In the PPS composite material of this invention, the test method for the average retained particle size of the metallic filler is as follows: Take 3-5g of the PPS composite material sample and calcine it at 700℃ under a nitrogen atmosphere to remove the PPS resin. Then, dissolve the ash in distilled water, stir until evenly dispersed, and then uniformly disperse it in a petri dish. Use an optical microscope to test the filler in multiple random fields of view, ensuring sufficient coverage (at least 150 sets of data are required). Calculate the arithmetic mean of all measured particle sizes, which is the average retained particle size of the metallic filler.
[0026] Preferably, the density of the metallic filler is 5.0-10 g / cm³. 3 The powder is selected from metal powder or its oxide powder that is paramagnetic or magnetizable, and is more preferably at least one of iron powder, ferric oxide powder, and magnetite powder.
[0027] In the PPS composite material of the present invention, the metallic filler imparts a metallic knocking feel and magnetic properties to the material. The mass percentage content of the metallic filler is ≥45%, preferably 48-60% (for example, it can be 45%, 48%, 50%, 52%, 54%, 56%, 60% or any of the above proportions), and more preferably 47-55%.
[0028] Preferably, the mass ratio of glass fiber to metallic filler is 1:(2-6), more preferably 1:(3-4) (for example, it can be 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:5 or any range between the above ratios). By controlling the mass ratio of glass fiber to metallic filler, the material can satisfy the requirements of metallic impact and magnetic attraction while also taking into account the material's toughness, strength, and appearance.
[0029] The metallic filler of this invention can be an unmodified metallic powder filler or a surface-modified metallic powder filler. The surface modification can be by using a coupling agent or stearic acid. Commonly used coupling agents include silane coupling agents, titanate coupling agents, aluminate coupling agents, etc.
[0030] Preferably, the toughening agent is a GMA-type toughening agent, selected from at least one of ethylene-butyl methacrylate-glycidyl acrylate copolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer.
[0031] Preferably, the amount of toughening agent used is 3 to 5 parts.
[0032] Preferably, the toughening agent has a mass percentage content of 1.0% to 4.0% in the PPS composite material, and more preferably 1.5% to 3%.
[0033] According to actual performance requirements, the PPS composite material of the present invention further includes 0-10 parts by weight of other additives, wherein the other additives are selected from at least one of antioxidants, lubricants, plasticizers, release agents, and pigments.
[0034] Preferably, the antioxidant includes any one or a combination of at least two of hindered amine antioxidants, hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants.
[0035] For example, the antioxidants include, but are not limited to, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] (antioxidant 245), tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), and bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate (PEP36), etc.
[0036] Preferably, the lubricant includes any one or a combination of at least two of the following: ester lubricants, alcohol lubricants, hydrocarbon lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants.
[0037] For example, the lubricant includes, but is not limited to, vinyl bis-stearamide, erucamide, stearate, polyethylene wax, etc.
[0038] For example, the plasticizers include, but are not limited to, dioctyl phthalate (DOP), dioctyl adipate (DOA), tricresyl phosphate (TCP), etc.
[0039] For example, the release agent includes, but is not limited to, silicone oil, paraffin wax, polyethylene wax, polytetrafluoroethylene, etc.
[0040] This invention also provides a method for preparing the above-mentioned PPS composite material, comprising the following steps:
[0041] According to the formula, the components are mixed evenly and then extruded and granulated using a twin-screw extruder to obtain the PPS composite material.
[0042] Preferably, the melt blending is carried out in a screw extruder, which is a twin-screw extruder. The extrusion temperature of the screw extruder is 180-330℃, for example, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 285℃, 290℃, 300℃, 310℃, or 320℃, or specific values between these values. The screw speed is 200-500 rpm, for example, 210 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, or 500 rpm, or specific values between these values. This invention also provides a toy article comprising the above-described PPS composite material.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] This invention, through the synergistic compounding of various components in a composite material and by controlling the average retention length of glass fibers within a specific range, produces a PPS composite material that possesses good strength, toughness, and appearance, while also exhibiting a metallic feel and magnetic properties, making it a promising candidate for application in the toy industry. Detailed Implementation
[0045] The present invention will be further illustrated below through specific embodiments. The following embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following embodiments.
[0046] Unless otherwise specified, all materials used in this invention are commercially available or prepared using conventional methods. The sources of the raw materials used in this invention are as follows:
[0047] PPS-1 resin: PPS1150C, NHU; tested according to ISO1133-1-2022, the melt index is 65g / 10min at 300℃ and 2.16KG, and the sodium content is 1300ppm;
[0048] PPS-2 resin: PPS1350C, NHU; tested according to ISO1133-1-2022, the melt index is 82g / 10min at 300℃ and 2.16KG, and the sodium content is 830ppm;
[0049] PPS-3 resin: PPS 3418, NHU; tested according to ISO1133-1-2022, the melt index is 41 g / 10 min at 300℃ and 2.16 kg, and the sodium content is 488 ppm.
[0050] PPS-4 resin: It is obtained by blending and extruding PPS1150C with 0.34wt% sodium hydrosulfide. According to ISO1133-1-2022, the melt index is 74g / 10min at 300℃ and 2.16KG, and the sodium content is 2781ppm.
[0051] ABS resin: KF-740, melt index of 40g / 10min at 220℃ and 10KG, Kingfa Science & Technology.
[0052] Ferric oxide powder: average particle size 35μm, density 5.72g / cm³ 3 It was prepared by using ferric oxide and a ball mill.
[0053] Iron powder-1: RHFP300, average particle size 48μm, density 7.86g / cm³ 3 Henan Renzhihe New Materials Co., Ltd.
[0054] Iron powder-2: The powder was ball-milled using RHFP300 to an average particle size of 12 μm and a density of 7.86 g / cm³. 3 .
[0055] Magnet powder: Commercially available NdFeB40 magnetic powder, 100 mesh, from Hebei Chaoyue Metal Alloy Materials, directly ball-milled to an average particle size of 50μm and a density of 7.56g / cm³. 3
[0056] Alumina powder: DC3-CL2, average particle size 3μm, Xinjiang Sanrui Baide New Materials.
[0057] Glass fiber: ECS309A-3-H, diameter 8-10μm, sodium content 281ppm, Chongqing International;
[0058] Toughening agent: Ethylene-butyl methacrylate-glycidyl acrylate copolymer, PTW, DuPont;
[0059] Antioxidant: Antioxidant 1010 and Antioxidant 168 are compounded in a weight ratio of 1:2.
[0060] PPS composite materials are obtained through the following preparation method:
[0061] According to the formulation, PPS resin, metallic filler, toughening agent, and antioxidant are mixed evenly as the main feeder and glass fiber as the main and / or side feeder. The mixture is then extruded and granulated using a twin-screw extruder at an extrusion temperature of 280-330℃ to obtain the PPS composite material. The average retention length of the glass fiber is controlled by adjusting the ratio of main to side feeder glass fiber, the screw shear, and the screw speed.
[0062] Examples 1-4, 7, 9-10 and Comparative Examples 3-5, 7: all glass fiber was side-fed, and the screw speed was 400 ppm.
[0063] Example 5: 10% glass fiber main feed, 90% glass fiber side feed, screw speed 400ppm.
[0064] Examples 6 and 8: All glass fiber is side-fed, screw speed 200ppm.
[0065] Comparative Examples 1 and 6: All glass fiber was fed as the main feed, and the screw speed was 500 ppm.
[0066] Comparative Example 2: Fiberglass was entirely side-fed, and the screw speed was 150 ppm.
[0067] Performance testing methods:
[0068] Average retention length of glass fibers: Take 3-5g of PPS composite material sample and calcine it at 700℃ to remove the PPS resin. After removing the PPS resin, dissolve the ash in distilled water and stir until evenly dispersed. Then, evenly disperse the ash in a petri dish. Use an optical microscope to test the glass fiber length in multiple random fields of view, ensuring sufficient coverage of glass fibers (at least 150 glass fibers should be measured). Calculate the arithmetic mean of all measured lengths, which is the average retention length of the glass fibers.
[0069] The method for testing the average retained particle size of metallic fillers is as follows: Take 3-5g of PPS composite material sample and calcine it at 700℃ under a nitrogen atmosphere to remove the PPS resin. After removing the PPS resin, dissolve the ash in distilled water, stir until evenly dispersed, and then uniformly disperse it in a petri dish. Use an optical microscope to test the filler in multiple random fields of view, ensuring sufficient coverage (at least 150 sets of data are required). Calculate the arithmetic mean of all measured particle sizes, which is the average retained particle size of the metallic filler.
[0070] Tensile strength: Tested according to standard ISO 527-2:2012, tensile rate 10 mm / min;
[0071] Cantilever beam notched impact strength: tested according to standard ISO 180:2000 / Amd2:2013; notch type A, pendulum energy: 2.75J, laboratory environmental conditions: 23±2℃, 50±5%RH;
[0072] Metallic Impact Test: A 150mm long iron rod with a diameter of 8mm was used to strike a 100*100*3mm PPS composite material sample fixed to a flat surface using a clamp. The sound was compared with that of an iron plate and an unfilled polypropylene board of the same size. The main comparisons were made of the material's timbre, loudness, pitch, and reverberation. If the sample's sound was crisp, loud, high-pitched, and had a long reverberation, and was as close as striking an iron plate, the material was considered to have a stronger metallic impact test. The sound of the polypropylene board was set to level 0, and the sound of the iron plate was set to level 5, with a gradient of 0.5. The average score from three people was used as the criterion; the higher the score, the stronger the metallic impact test.
[0073] Magnetic attraction: A ferrite magnetic rod with a diameter of 1 cm and a length of 12 cm, whose surface magnetic field strength is measured to be 500 G using a gaussmeter, is brought close to a 1 g PPS composite material sample. If the sample can be attracted and suspended in the air, the magnetic force of the material is considered to meet the requirements (Y); otherwise, the magnetic force is considered to be insufficient (N).
[0074] Appearance: A 100*100*2.0mm square sheet was injection molded, and its appearance was evaluated by observation. The specific method was as follows: At an injection temperature of 280-310℃, using 50% of the injection speed and 50% of the pressure, and at a mold temperature of 130℃, the PPS resin composition was injection molded into the square sheet. The presence of obvious floating fibers was observed. If obvious floating fibers were present, the appearance was deemed unacceptable (N); if no obvious floating fibers were present, the appearance was deemed acceptable (Y).
[0075] Table 1. Components (parts by weight) and test results of PPS composite materials in Examples 1-8
[0076]
[0077] Table 2. Components (parts by weight) and test results of PPS composite materials in Examples 9-10 and Comparative Examples 1-7.
[0078] In Comparative Example 1, the average retention length of the glass fibers was too short, resulting in a significant decrease in the mechanical properties of the material.
[0079] In Comparative Example 2, the average retention length of the glass fiber was too long, resulting in a large number of loose fibers in the composite material and a poor appearance.
[0080] In Comparative Example 3, the amount of glass fiber added was too low, resulting in the material's mechanical properties failing to meet requirements.
[0081] In Comparative Example 4, the composite material prepared using ABS resin had a weak metallic impact feel, and its mechanical properties and appearance also failed to meet the requirements.
[0082] In Comparative Example 5, the magnetic attraction of the composite material prepared by using alumina powder did not meet the requirements.
[0083] In Comparative Example 6, the average retention length of glass fibers and the weight content of sodium in the composite material are not within the scope of this invention, resulting in a significant decrease in the mechanical properties of the material.
[0084] In Comparative Example 7, the amount of toughening agent was too low, which led to a significant decrease in the notched impact strength of the cantilever beam of the material.
[0085] As can be seen from the results of the examples, the present invention, through the synergistic compounding of the components in the composite material and by controlling the average retention length of the glass fiber within a specific range, prepares a PPS composite material that has good strength, toughness and appearance, while also having a metallic feel and magnetic properties.
Claims
1. A PPS composite material, characterized in that, Based on 100 parts by weight of metallic filler, the composite material contains 20-40 parts of glass fiber, 50-80 parts of PPS resin, and 2-8 parts of toughening agent, wherein the average retention length of the glass fiber in the PPS composite material is 200-400 μm.
2. The PPS composite material according to claim 1, characterized in that, The PPS resin has a melt index of 50-200 g / 10 min at 300℃ and 2.16 kg, and the melt index is tested according to ISO 1133-1-2022.
3. The PPS composite material according to claim 1, characterized in that, The average retained particle size of the metallic filler is 10-60 μm, preferably 20-50 μm; the density of the metallic filler is 5.0-10 g / cm³. 3 .
4. The PPS composite material according to claim 3, characterized in that, The metallic filler is a paramagnetic or magnetizable metal material and its oxide. Preferably, the metallic filler is selected from at least one of iron powder, ferric oxide powder, and magnetite powder.
5. The PPS composite material according to claim 1, characterized in that, The mass ratio of glass fiber to metal filler is 1:(2-6), preferably 1:(3-4).
6. The PPS composite material according to claim 1, characterized in that, The sodium content in the PPS composite material is 230-800 ppm by weight, preferably 300-700 ppm.
7. The PPS composite material according to claim 1, characterized in that, The toughening agent is a GMA-type toughening agent, selected from at least one of ethylene-butyl methacrylate-glycidyl acrylate copolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer.
8. The PPS composite material according to claim 1, characterized in that, The product also includes 0-10 parts by weight of other additives, which are selected from at least one of antioxidants, lubricants, plasticizers, mold release agents, and pigments.
9. A method for preparing the PPS composite material according to any one of claims 1-8, characterized in that, Includes the following steps: According to the formula, the components are mixed evenly and then extruded and granulated using a twin-screw extruder to obtain the PPS composite material.
10. A toy article comprising the PPS composite material as described in any one of claims 1-8.
Citation Information
Patent Citations
Foamed polyphenylene sulfide composition as well as preparation method and application thereof
CN114231031A
Glass fiber reinforced ABS (Acrylonitrile Butadiene Styrene) composition as well as preparation method and application thereof
CN115895171A
Polypropylene metal composite material as well as preparation method and application thereof
CN120289907A
Imitation metal engineering plastic composite material and preparation method of the same
US20120059100A1
Glass fiber group and glass fiber reinforced resin-based composite material
WO2021077849A1